2003
DOI: 10.12968/hosp.2003.64.7.2311
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation: attitudes and perceptions of junior doctors

Abstract: Many junior doctors feel cardiac arrests are unsatisfactorily managed and experience high levels of stress during the procedure, often feeling they are inadequately trained for the task. Juniors also regard ‘do not resuscitate’ orders as decisions for teams, not individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
2
12
0
1
Order By: Relevance
“…Residents felt significantly more comfortable about their resuscitation skills and were more confident at the end of the year of mock codes regardless of the level of training. These findings are similar to two studies involving internal medicine resident's perceptions about cardiac arrests (Scott et al 2003;Hayes et al 2007). This improved confidence is likely attributable to the experience of direct patient care as opposed to mock code participation.…”
Section: Discussionsupporting
confidence: 86%
“…Residents felt significantly more comfortable about their resuscitation skills and were more confident at the end of the year of mock codes regardless of the level of training. These findings are similar to two studies involving internal medicine resident's perceptions about cardiac arrests (Scott et al 2003;Hayes et al 2007). This improved confidence is likely attributable to the experience of direct patient care as opposed to mock code participation.…”
Section: Discussionsupporting
confidence: 86%
“…11 This may avoid the situation where a patient requests CPR despite explanation of its futility: the guidelines acknowledge that a doctor cannot be required to give treatment contrary to their clinical judgement and if a doctor feels that the harm of the discussion outweighs the benefits there should be no moral imperative to discuss CPR. 1 6 12 13 Doctors may also experience difficulty discussing these issues (one study showed that 72.8% of doctors find discussions stressful 14 ) and there is a reduction in the documentation of DNAR decisions where patient discussion is mandatory. Although the claimant, Mr Burke, was concerned about doctors withdrawing artificial nutrition and hydration as his degenerative neurological disease progressed, the initial ruling that doing so was unlawful and in breach of his human rights had wider implication which would have included patients demanding CPR against the judgement of health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Despite completion of these courses, trainees experience significant stress in real-life situations as they feel unprepared to deal with such clinical emergencies. [5][6][7] Increasing trainee numbers, decreasing training hours and an overall impetus to shorten training curriculum have all contributed to an overall reduction in clinical exposure. In order to address this issue, simulation is increasingly used as an educational tool.…”
Section: Introductionmentioning
confidence: 99%